The Connectivity Between Leap Motion And Android Smartphone For Augmented Reality (AR)-Based Gamelan - Permana, Frihandhika; Tolle, Herman; Utaminingrum, Fitri; Dermawi, Rizdania (Journal of Information Technology and Computer Science, 2018)
The smartphone development today makes the gadget not only used as a communication tool but also as an entertainment tool such as to play games and play music. The development of the smartphone also supports many technologies that can be run on the smartphone itself, such as Augmented Reality (AR), for example. There are some studies evaluated the AR application combined with Leap Motion, but those studies were using the SDK alpha of the Leap Motion Corp. that is now no longer accessible for the developers to use. This research is meant to overcome such a problem. The method proposed in this study is a technique to connect the Leap Motion with Android for Augmented Reality application. This paper also evaluates the technique used to connect the AR technology to Leap Motion so it can be a visual instrument simulation, which applied to the Gamelan traditional music instrument. The experiments resulted in the accuracy rate of the application of 96.43% for right-hand movement and 97.86% for the left-hand motion. The high accuracy result obtained in the research can be a promising result for the future research.